Survey of Antibiotic-producing Bacteria Associated with the Epidermal Mucus Layers of Rays and Skates - Ritchie, Kim B.; Schwarz, Melbert; Mueller, Joseph; Lapacek, Valeri A.; Merselis, Daniel; Walsh, Catherine J.; Luer, Carl A. (Frontiers in Microbiology, 2017)
Elasmobranchs represent a distinct group of cartilaginous fishes that harbor a remarkable ability to heal wounds rapidly and without infection. To date very little work has addressed this phenomenon although it is suggested that antibiotic capabilities associated with epidermal surfaces may be a factor. The study of benefits derived from mutualistic interactions between unicellular and multicellular organisms is a rapidly growing area of research. Here we survey and identify bacterial associates of three ray and one skate species in order to assess the potential for antibiotic production from elasmobranch associated bacteria as a novel source for new antibiotics.